Nestor, Barbara (audio interview #10 of 10) - Nestor, Barbara (9/29/1884 - 11/1/1979); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - By the time of this ninth interview with Barbara Nestor she seemed to have recovered more fully from her illness. Although there did not seem to be any memory difficulties, there are a few occasions when she repeats information provided in previous interviews. The audio quality of the interview is fair, though there are a few areas in the second tape where the recording includes a series of skips. 4/4/1975